(untitled) (Community Based Medical Journal, 2021)
Laparoscopic cholecystectomy (LC) has become the gold standard for the surgical treatment of gallbladder disease, but conversions to open cholecystectomy are still inevitable in certain cases. Knowledge about the rate and underlying reasons for conversion could help surgeons during preoperative assessment and improve the informed consent of patients. We decide to review the rate and causes of conversion of our LC series. This study included 320 consecutive laparoscopic cholecystectomies from January 2017 to December 2019 at Community Based Medical College Hospital Bangladesh, Mymensingh. All patients had surgery performed by same surgeon. Conversion to open cholecystectomy required in 15 (4.6%) patients. Out of 15 cases, the highest number of patients 10(66.6%) were in age group 50 to 59 years with a mean age of 60.1 years and standard deviation (SD) of 9.8 years. Of them 9 (60%) were male. The most common reasons for conversion of them were severe adhesions at calot’s triangle 6 (40%) and acutely inflamed gallbladder 5 (33.3%), bleeding 2 (13%). No surgical procedures are complication free. The most common complication was superficial wound infection 8(2.5%). Delayed complications seen in our series is port site incisional hernia 2 (0.62%). Male gender, age older than 60 years, previous upper abdominal surgery, diabetes, and severity of inflammation were all significantly correlated with an increased conversion rate to laparotomy. LC is the preferred method even in difficult cases. This study emphasizes that although the rate of conversion to open surgery and complication rate are low in experienced hands, the surgeons should keep a low threshold for conversion to open surgery. CBMJ 2020 July: Vol. 09 No. 02 P: 14-18